Method for virus propagation in a bioreactor - Mel, Maizirwan; Esa, Noorhayati (2012)
THE PRESENT INVENTION RETATES TO A METHOD FOR VIRUS PROPAGATION IN A BIOREACTOR (10) COMPRISING THE STEPS OF: FIRSTLY; CULTURING A CELL IN A BIOREACIORTO PRODUCE MORE CELLS TO FORM A BIOREACTOR CULTURE IN THE PRESENCE OF MTCROCARRTERS (11), WHERETN THE BTOREACTOR rS A SPTNNER VESSEL OR STIRRED TANK BTOREACTOR; THEN, INOCULATING THE CETIS WTTH VIRUS (12); AND SUBSEQUENTLY, INCUBANNG THE VIRUS WITH THE BIOREACTOR CULTURE (13), WITH TEMPEMTURE OF 37"C, AGTTATION SPEED OF 30-70 RPM, PH 7.2, AND DISSOLVED OXYGEN CONTENT (PO2) OF 30olo; WHEREIN THE WRUS IS NEWCASTT"E DISEASE VIRUS (NDV) AND THE CELLS ARE VERO CELLS.